Transcriptomic insights into the interplay between polyketide biosynthesis and other secondary metabolite biosynthetic clusters and biological pathways in entomopathogen Beauveria bassiana - Toopaang, Wachiraporn; Yoocha, Thippawan; Naktang, Chaiwat; Wichienchote, Nuchnudda; Pechsrichuang, Phornsiri; Tangphatsornruang, Sithichoke; Tanticharoen, Morakot; Yang, Yu-Liang; Amnuaykanjanasin, Alongkorn (Frontiers in Microbiology, 2025)
Background and aimsThe polyketide synthase gene pks15 plays a critical role in insect virulence and cell wall formation in the entomopathogenic fungus Beauveria bassiana. Metabolomics studies have also shown that this gene exhibits crosstalk with other biosynthetic clusters of beauvericins, bassianolide, enniatin A, and ferricrocin. Here, we investigated the cross-pathway communication of pks15 biosynthetic cluster and other secondary metabolite clusters and biological pathways using transcriptomes.MethodsTwo comparative transcriptomic analyses were conducted, one compared the wild-type B. bassiana-injected beet armyworm (WT in vivo) with Δpks15 mutant-injected beet armyworm (Δpks15 in vivo), and the other one compared WT in vivo with wild-type grown in vitro. Insect inoculation was performed by intrahemocoelic injection of conidia, hence bypassing the cuticular penetration.ResultsThe transcriptomic profile of Δpks15 in vivo revealed significant downregulation of genes involved in mycotoxin production, secondary metabolite biosynthesis, and cell wall integrity compared to the WT in vivo. Notably, 36 out of 45 secondary metabolite biosynthetic clusters in B. bassiana BCC 2660, were downregulated in Δpks15 in vivo, suggesting marked changes in the biosynthesis of secondary metabolites after pks15 deletion. These clusters included genes encoding nonribosomal peptide synthetase, transporters, glycosylation, proteolysis, peptidase activity, signal peptides, and cell wall and surface proteins. Our findings indicate that pks15 plays an important role in fungal development and pathogenicity. Within the pks15 cluster, the UDP-glucosyl transferase gene Bbugt1 was consistently upregulated 3-fold in the WT in vivo compared to the WT in vitro armyworm group 48–96 h post-inoculation. In contrast, Bbugt1 was downregulated in Δpks15 in vivo compared to the WT in vivo during the same period. This regulation pattern suggests that Bbutg1 plays a role in the production or modification of secondary metabolites, specifically during the host infection.ConclusionThis study provides the first transcriptomic evidence that the pks15 cluster regulates multiple secondary metabolite clusters, including bassianolide, siderophores, tenellin, oosporein, and several unidentified PKS and NRPS clusters. Additionally, pks15 is associated with fungal cell wall remodeling and immune evasion. Our work uncovers an expanded regulatory role for PKS15, revealing novel connection between metabolite biosynthesis and virulence-associated processes, and offering opportunities for targets for biocontrol improvement and metabolite engineering.